Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Cerita Bangun Ruang Kelas V SDN Slipi 15 Pagi - Dinda Pratiwi; Tiurlina; Fatihaturosyidah (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This research is motivated by the low ability of VC class students at SDN Slipi 15 Jakarta in understanding the problems in the story. Most students have difficulty in solving story problems so that many errors are found in solving them. The errors in this study will be analyzed based on the Newman procedure. The procedure consists of 5 types of errors, namely reading errors, comprehension errors, transformation errors, process skill errors, and finally, encoding errors. The type in this research is descriptive qualitative. This study aims to describe students' errors in solving story problems with the volume of cubes and blocks and the factors that cause them. The subjects in this study were 24 students of VC class who made mistakes according to Newman's procedure. The instrument used in this study is the author himself and assisted by story test questions in the form of a description of 3 questions, semi-structured interviews, and documentation in the form of photos and interview recordings. The results showed that all VC class students made mistakes so that as many as 24 students would be interviewed to find out the cause. The errors that occur are reading errors as much as 22.2%, understanding errors as much as 55.5%, transformation errors as much as 50%, processing skills errors as much as 100%, and writing errors in the final answer as much as 100%. The causative factor is the student's personal factor, the concept mastery factor, and the reading and writing ability factor. The solution that can be done is to apply habituation of problem solving strategies using the Newman procedure, provide story questions exercises, and can apply multiplication suits to improve students' numeracy skills.